The OMERACT Core Set of Domains for Outcome Measures in Behçet Syndrome - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER (My University, 2020)
OBJECTIVE: There is an unmet need for reliable, validated, and widely-accepted outcome measures for randomized clinical trials in Behçet syndrome (BS). The Outcome Measures in Rheumatology Clinical Trials (OMERACT) BS Working Group, a large, multi-disciplinary group of experts in BS and patients with BS, worked to develop a Core Set of data-driven outcome measures for use in all clinical trials of BS. METHODS: The Core Domain Set was developed through a comprehensive, iterative, multi-stage project which included a systematic review, a focus group meeting and qualitative patient interviews, a survey among experts in BS, a Delphi exercise involving both patients and physician-experts in BS, and utilization of the data, insight, and feedback generated by these processes to develop a final Core Domain Set. RESULTS: All steps were completed and domains were delineated across the organ systems involved in this disease. Since trials in BS often focus on specific manifestations and not the disease in its entirety, the final proposed Core Set includes 5 domains mandatory for study in all trials in BS (disease activity, new organ involvement, quality of life, adverse events, and death) with additional sub-domains mandatory for study of specific organ-systems. The final Core Set was endorsed at the 2018 OMERACT meeting. CONCLUSION: The Core Set of Domains in BS provides the foundation through which the international research community, including clinical investigators, patients, biopharmaceutical industry, and government regulatory bodies can harmonize the study of this complex disease, compare findings across studies, and advance development of effective therapies.